Initial Education for Immigrants' Children in Spain's "Welcoming Schools" - María del Pilar Quicios García; Isabel Miranda Vizuete (Universidad Autónoma de Baja California, 2005)
This article describes the initial training received by immigrants' children arriving in Spanish schools. It also shows the reality they encounter during their first months of schooling. These students have three hallmarks: ignorance of the Spanish language or a low level of understanding; curricular lag of more than two academic years; or no previous schooling in their countries of origin. Aiming to palliate these deficiencies, and to offer these children some guarantee of success in their studies, the administration's Board of Education has decided to enroll them temporarily in a series of classrooms designed specifically for them: the "Welcoming Schools". These classrooms are an innovative educational answer launched in January, 2003, and now beginning to bear fruit.